Bilateral Cemented Custom-Made Total Hip Arthroplasty in Paget's Disease with Femoral Cortical Thickening and Canal Narrowing - D'Ambrosi, Riccardo; Ballini, Luca; Valli, Federico; Guarino, Stefano; Rubino, Maurizio; Ursino, Nicola (Joints, 2019)
In this report, we present a case of a 57-year-old man complaining of pain in both his hips. Clinically, the patient reported lameness and reduction in the range of motion of the hips. Radiographic imaging showed a very narrow medullary femoral canal, confirmed by a computed tomography scan. In consideration of the narrowness of the femoral canal and cortex thickening, and due to the rarity of the clinical case, we opted to use a custom-made prosthesis. We performed total hip arthroplasty, initially on the right side. One year later, we repeated the procedure on the left side. One year after the last surgery, the patient reported well-being and continuous improvement in walking, with no complications. This case report highlights the features and the critical issues related to this kind of surgery in patients affected by Paget's disease of the bone and the importance of custom-made implants in challenging cases.
Keywords: Paget's disease; rare disease; custom-made hip arthroplasty; femoral cortical thickening; canal narrowing